RFID within High-Tech Clusters – Towards a Knowledge-Based Economy - Bembenek Boguslaw (Economics and Business)
- The concept of knowledge-based economy (KBE) in this article constitutes the basis for the undertaken considerations regarding the implementation of Radio Frequency Identification (RFID) technology in the development process of high-tech clusters. It has been indicated in the article that this type of economy is characterised by quick development, particularly, of these disciplines which are related to information processing and science development, mainly the high-tech industry, including the technologies and services of an information society. It has been emphasised that in these market conditions the key sources of competitive advantage of business entities comprise, inter alia, the efficiency of knowledge management as well as various knowledge-intensive undertakings, which create newer and newer value for key stakeholders. The main subject of this paper is to analyse the development and application of RFID within the high-tech cluster. Firstly, the paper aims to present a literature review on the strategic importance of RFID technology for firms located in high-tech clusters through tracing a broad range of literature. Secondly, it constitutes an attempt to characterise the factors determining the decision to implement this